2005
DOI: 10.1088/0022-3727/38/18/004
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of polypyrrole-coated iron oxide nanoparticles

Abstract: Iron oxide nanoparticles were prepared by sol -gel process. In-situ polymerization of pyrrole monomer in the presence of oxygen in iron oxide -ethanol suspension resulted in a iron-oxide polypyrrole nanocomposite. The structure and magnetic properties of the nanocomposites with varying pyrrole concentrations are investigated. The X-Ray diffraction studies indicate the presence of γ − F e 2 O 3 phase for the concentrations investigated. FTIR studies confirm the presence of polypyrrole. The TEM studies show aggl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Therefore, conjugated polymers combined with magnetic nanoparticles to form ferromagnetic nanocomposites provide an exciting system to investigate the possibility of exhibiting novel functionality to provide the better microwave absorption properties. Number of articles reported the synthesis and electrical properties of polymer nanocomposites of polypyrrole and polyaniline incorporating ferrite particles in the polymer matrix [20][21][22][23][24][25]. Bidan et al has reported the electrochemical method to prepare polypyrrole composite exhibiting magnetic and conducting properties [26].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, conjugated polymers combined with magnetic nanoparticles to form ferromagnetic nanocomposites provide an exciting system to investigate the possibility of exhibiting novel functionality to provide the better microwave absorption properties. Number of articles reported the synthesis and electrical properties of polymer nanocomposites of polypyrrole and polyaniline incorporating ferrite particles in the polymer matrix [20][21][22][23][24][25]. Bidan et al has reported the electrochemical method to prepare polypyrrole composite exhibiting magnetic and conducting properties [26].…”
Section: Introductionmentioning
confidence: 99%
“…The use of nanoparticles is often limited by their low solubility in most organic solvents which leads to phase separation or sedimentation of the particles from the matrix or by the poor miscibility of all components. There are several ways to overcome the low solubility of the nanoparticles and to increase the chemical compatibility between the single components: (i) by in situ formation of the nanoparticles in a prepolymeric matrix [4], (ii) by adding ligands to form core/shell like nanoparticles or (iii) by polymeric particle coating [5][6][7][8]. It is known that the particle size is an important factor as well as the interface region between filler and matrix for the macro or micro optical and mechanical or other new properties of the formulated composites.…”
Section: Introductionmentioning
confidence: 99%
“…This -OH group with hydrogen bonding is coming from starch. Peaks between 400 and 700 cm -1 correspond to Fe-O bonds (Raksha Sharma et al 2005).…”
Section: Ft-ir Studiesmentioning
confidence: 99%